KOMPOSISI DAN STRUKTUR VEGETASI HUTAN MANGROVE DI DESA SAPA KABUPATEN MINAHASA SELATAN (COMPOSITION AND STRUCTURE VEGETATION OF MANGROVE FOREST IN SAPA VILLAGE, SOUTH MINAHASA DISTRICT) - Indra G. Ndede; Dr. Ir. Johny S. Tasirin, MScF.; Ir. Maria Y.M.A. Sumakud, MSc. (Universitas Sam Ratulangi, 2017)
ABSTRACTThis study aimed to determine the composition of the species and structure of mangrove forests in Sapa Village South Minahasa District. The study was conducted in October-November 2016. The Important Value Index (INP) obtained from vegetation analysis was used as an indicator to describe the composition and structure of mangrove forest. Plot assisted path method is used in vegetation analysis. Created 10 lane hayal with a width of 200 m divided into 10 segments, there are 69 plots to obtain data and species of mangroves. This study showed that 7 species from 4 mangrove families in Sapa Village, namely : Rhizophoraceae (Ceriops Tagal, Rhizophora mucronata, Rhizophora apiculata, Bruguiera gymnorhiza), Sonneratiaceae (Sonneratia alba), Avicenniaceae (Avicennia officinalis), Meliaceae (Xylocarpus granatum). Species with the highest INP values are Sonneratia alba at all growth rates, trees with INP values of 178.63%, stakes 101.14%, and 65.37% seedlings. The mangrove trees in Sapa village are found in a diameter range of 10 to 20 cm.Keywords : composition and structure vegetation, Sapa Village.